A influência da inteligência emocional no desempenho organizacional: uma revisão sistemática - Lima, Elian Curico de (Brasil, 2024)
Emotional Intelligence (EI) is one of the branches of psychology applied to people management that has become increasingly important in the corporate environment. EI was initially defined by Salovey and Mayer (1990), who were pioneers in presenting it in terms of five skills: knowing one's own emotions, dealing with emotions, motivating oneself, recognising emotions in others and dealing with relationships. Goleman (1995) refined this definition, emphasising these aptitudes as emotional and social skills. The aim of this study was to investigate, by means of a Systematic Literature Review (SLR), the existence and nature of the relationship between Emotional Intelligence and Organisational Performance (OP). As far as methodological issues are concerned, this is a qualitative study and its results were analysed using elements of Bardin's Content Analysis (2007), with the necessary adaptations. The study adopts Paul and Criado's (2020) Theory-Based Review classification and follows the sequence suggested by Tranfield, Denyer and Smart (2003), who presented a study discussing the Systematic Literature Review in the area of Management. The main results showed that, based on the studies identified and analysed, there is a positive and impactful relationship between EI and DO, indicating that EI has become increasingly valued in the job market, especially for people in leadership positions, showing that EI plays a crucial role in leadership effectiveness. The results also show that EI is positively linked to productivity, job satisfaction and a reduction in stress and anxiety in the workplace, as shown in some studies. It can therefore be concluded that organisations that invest in developing the EI of their leaders tend to see significant improvements in employee performance and satisfaction, resulting in a positive impact on organisational performance as a whole.